2010
DOI: 10.1590/s0034-70942010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da hemodiluição normovolêmica aguda na coagulação sanguínea: comparação entre os testes colhidos de um modelo in vivo e de um modelo in vitro

Abstract: Summary: Souza MAB, Klamt JG, Garcia LV -Effects of Acute Normovolemic Hemodilution on Blood Coagulation: Comparison between Tests of an In Vivo and an In Vivo Models. Background and objectives:Normovolemic hemodilution produces conflicting results on hemostasis, since works differ according to the fluids used, degree of hemodilution, method used to evaluate hemostasis, and the way used to produce hemodilution. The effects of hemodilution on hemostasis can depend on how it is done and whether an in vivo or an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…associated parameters should be considered to minimize possible complications. 11 Previous studies have shown that the need for blood transfusion may be reduced by the use of acute normovolemic hemodilution, [12][13][14] and prophylactic intravenous administration of concentrated fibrinogen or tranexamic acid immediately before and after myocardial revascularization, which reduces the frequency of postoperative bleeding and fibrinolysis in high-risk populations. [15][16][17] Other methods such as the use of intraoperative autotransfusion in CPB cardiac surgery, hemofiltration, preoperative autologous blood donation and erythropoietin pretreatment, as well as the recognition of normovolemic anemia, have been described to reduce blood transfusion and its potential adverse effects.…”
Section: Transfusion Parametersmentioning
confidence: 99%
“…associated parameters should be considered to minimize possible complications. 11 Previous studies have shown that the need for blood transfusion may be reduced by the use of acute normovolemic hemodilution, [12][13][14] and prophylactic intravenous administration of concentrated fibrinogen or tranexamic acid immediately before and after myocardial revascularization, which reduces the frequency of postoperative bleeding and fibrinolysis in high-risk populations. [15][16][17] Other methods such as the use of intraoperative autotransfusion in CPB cardiac surgery, hemofiltration, preoperative autologous blood donation and erythropoietin pretreatment, as well as the recognition of normovolemic anemia, have been described to reduce blood transfusion and its potential adverse effects.…”
Section: Transfusion Parametersmentioning
confidence: 99%